Improving Students Motivation in Learning English Vocabulary Using Online Games - Muhamad Sofian Hadi; Lidiyatul Izzah; Sulthan Caraka Adipradana (English Language Education Department, Universitas Majalengka, 2022)
This article is a product of a research study conducted and aimed to demonstrate the effect of online games to motivate students in learning english vocabulary, with participants of 5 senior highschool students from various school and using qualitative approach as the method. The result on improving students motivation in learning english vocabulary using online games had quiet effective not only it helps students, it also make learning vocabulary more interesting, fun and also relaxing, as for online games itself in this internet era helps students connect and play, they have been proved in the educational field as a possible learning mediation, so in the future online games will not only be considered as hindrance for students to study, but an alternative place for students to learn more.